Hydrolyzed Protein Formula for Allergy Prevention in Preterm Infants: Follow-Up Analysis of a Randomized, Triple-Blind, Placebo-Controlled Study - Di Mauro, Antonio; Baldassarre, Maria Elisabetta; Brindisi, Giulia; Zicari, Anna Maria; Tarantini, Martina; Laera, Nicla; Capozza, Manuela; Panza, Raffaella; Salvatore, Silvia; Pensabene, Licia; Fanelli, Margherita; Laforgia, Nicola (Frontiers in Pediatrics, 2020)
Background: Allergic diseases are a major public health burden worldwide. Evidence suggests that early nutrition might play a key role in the future development of allergies and the use of hydrolysed protein formulas have been proposed to prevent allergic disease, mainly in term infants with risk factors. Aim: To evaluate the preventive effect of an hydrolysed protein formula versus an intact protein formula on allergy development in preterm infants with or without risk factors. Methods: We performed a 3-year follow-up study of a previous triple-blind, placebo-controlled randomized trial. Evidence of atopic dermatitis, asthma and IgE-mediated food allergies were evaluated according to a validated parental questionnaire (Comprehensive Early Childhood Allergy Questionnaire). Food sensitisation was also investigated by skin prick test at 3 years of chronological age. Results: Of the 30 subjects in the intact protein formula group and 30 in the extensively hydrolysed formula group, respectively 18 and 16 completed the 3-year follow-up and entered the final analysis. No group differences in the incidence of atopic dermatitis, asthma, IgE-mediated food allergies and food sensitisation were found. Conclusion: Despite the small number of cases, extensively hydrolysed protein formula seems to be ineffective in allergic diseases prevention in preterm neonates. Further adequately powered, randomized controlled trials evaluating hydrolysed protein formula administration to prevent allergic diseases in preterm neonates are needed.